Solusi Inovatif Mesin Peras Santan dan Oven Serbaguna untuk Peningkatan Kualitas VCO - Sri Prilmayanti Awaluddin; Januar Kulsaputro; Saldy Hapiwaty; Muntasir Muntasir (Penerbit Goodwood, 2026)
Purpose: This study analyzes the effectiveness of a coconut milk pressing machine and multi-purpose oven in improving the quality, production capacity, and income of the Kitasuka Virgin Coconut Oil (VCO) Micro-Business. Methodology: The research used a mixed-methods approach based on Participatory Action Research (PAR) at the Inaayu Natural Micro-Business, Pangkep Regency. Data were collected through observation, interviews, and documentation, then analyzed descriptively and qualitatively. Results: The technology implementation successfully increased VCO production capacity from 250-300 liters per month to 300-500 liters. Partners' average monthly income rose significantly from IDR 35.5 million to IDR 63 million. The VCO quality also improved in clarity, shelf life, and production hygiene. Conclusions: The innovative technologies effectively boosted the micro-business's production capacity and product quality, leading to a substantial increase in monthly revenue. The PAR approach, which actively involved partners, was key to the program's success and sustainability. Limitations: This research was limited to a single micro-enterprise location and a relatively short time period. Generalizing the findings requires further study with a broader scope. Contributions: This research makes a practical contribution to the development of agro-industrial micro-enterprises through the application of appropriate technology. Academically, it enriches the literature on technology-based community empowerment and production innovation in small-scale industries.